KALINGA STYLE ART AND ARCHITECTURE OF FOUR HINDU TEMPLES OF THE COASTAL BELT OF ODISHA IN EASTERN INDIA - Mohapatra, Ratnakar; Beruk, Chiranjibi (International Journal of Psychosocial Rehabilitation, 2020)
Odisha is a land of temples and it is also believed to be the centre of panchadevapasana of Hinduism. All through the ages, the coastal belt of Odisha has retained a cultural uniqueness much more prominent than her geographical situations. The extant Hindu temples of the coastal belt of Odisha represent the Kalinga style temple architecture of Odisha. The art and architectures of the Hindu temples of the coastal belt of Odisha draw the attention of present scholars to start the research work. The four Hindu temples of the coastal belt of Odisha are such as 1. Narayana Temple at Vishnupur, 2. Dakshina-Chandi temple at Mangalapur, 3. Chitresvari temple at Chitreswari and 4. Dakshinesvara temple at Begunia. All the above four temples of the coastal belt of Odisha are not seriously undertaken by any art historians for scholarly works. The present article attempts to highlight the detailed art and architecture along with the sacredness of the four Hindu temples of the coastal belt of Odisha in Eastern India. The earlier art historians had left these Hindu temples for the scholarly works, for which the present scholars have undertaken research work in this respect. Here, both the primary and secondary sources are meticulously utilized for the systematic writing of this article.